Bio-based boronic ester vitrimer for realizing sustainable and highly thermally conducting nanocomposites. (September 2022) - Shi, Yongming; Hong, Younggi; Hong, Jiyae; Yu, Ayoung; Lee, Min Wook; Lee, Jiyoung; Goh, Munju
Abstract: Bio-based vitrimers prepared using tannic acid, glycerol, and boric acid exhibited the properties of a hard solid and a viscoelastic liquid at low and high temperatures, respectively. The degree of boronic ester bonding increased in the presence of NaOH and cellulose nanofibers, giving an increased tensile strength and hardness. The optimal nanocomposite exhibited a higher thermal conductivity than organic-based polymers. Composites with Al2 O3 and hexagonal boron nitride fillers gave extremely high thermal conductivities. A thermally conducting grating was also prepared using different thermally conducting vitrimers. Acidic treatment of the nanocomposite recovered the filler, indicating the application potential of these materials. Graphical abstract: Image 1 Highlights: Bio-based vitrimers were prepared using tannic acid, glycerol, and boric acid. Additional boronic ester bonds formed in the presence of NaOH/cellulose nanofibers. The optimal nanocomposite exhibited a higher thermal conductivity than epoxy resin. Added Al2 O3 and h -BN fillers led to extremely high thermal conductivities. Acid treatment recovered the filler to show the usage potential of these materials.